PENGARUH PERSEPSI KEMUDAHAN TERHADAP MINAT NASABAH DALAM PENGGUNAAN RAYA DIGITAL BANK DI PT BANK RAYA INDONESIA Tbk. JAKARTA - Erlita Khrisinta Dewi; Erick Lauren Ray; Fitri Ardanih (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the perception of convenience, customer interest, and the effect of perceived convenience significantly on customer interest in using Raya Digital Bank at PT Bank Raya Indonesia Tbk in Jakarta. The approach used is a quantitative approach. This research uses descriptive analysis. The data used in this study is primary data with the method of distributing questionnaires. The sample used is 97 respondents who have customer criteria from Bank Raya Indonesia and use the Raya Digital Bank application. The test was carried out through instrument testing, correlation coefficient, determination coefficient, and T test. The results of the correlation coefficient test of the R value obtained were 0.733 so that it was known that the perceived convenience variable had a strong relationship with customer interest. The coefficient of determination test obtained R square results of 0.538 so that it can be seen that the ability of the perceived ease variable in explaining the variable of customer interest in using Raya Digital Bank is 0.538. The results also show that the perception of convenience has a significant and positive effect on customer interest in using Raya Digital Bank at PT Bank Raya Indonesia Tbk Jakarta.